A Janus Separator for Inhibiting Shuttle Effect and Lithium Dendrite in Lithium−Sulfur Batteries. Issue 4 (28th January 2022) - Xiao, Ru; Yang, Shan; Yu, Tong; Hu, Tianzhao; Zhang, Xiaoyin; Xu, Ruogu; Wang, Yaozu; Guo, Xiaodong; Sun, Zhenhua; Li, Feng
Abstract: Lithium−sulfur (Li−S) batteries are promising candidates for next‐generation energy storage systems. However, unsurpassed challenges including the shuttle effect and Li dendrite growth are still faced for marketization. Herein, La2 Zr2 O7‐ x (OV‐LZO) nanotubes with surface oxygen vacancies were fabricated to serve as Janus separator coatings for Li−S batteries. The overlapping OV‐LZO nanotubes construct an efficient lithium polysulfides adsorption and catalysis network at the interface of the cathode/separator and a Li + transport network by increasing the Li + transfer number and boosting Li + diffusion at the interface of the anode/separator to tackle the shuttle effect and lithium dendrite issues. The excellent thermal stability of OV‐LZO lowers the possibility of a short circuit. As a result, the elaborate Janus OV‐LZO coating enabled Li−S batteries with an areal capacity of 8.33 mAh cm −2 after 50 cycles at 0.2 C under conditions of high sulfur loading (9.1 mg cm −2 ), lean electrolyte (E/S of 4.5 mL g −1 ) and low N/P ratio of 2. Moreover, the gravimetric energy density of the battery was greatly increased compared to that of the commercial separator with little increase in the mass loading of separator. This strategy can be integrated with the optimization of other battery components to light the way for the construction of practical Li−S batteries. Abstract : Janus separator coatings for Li−S batteries : The designed La2 Zr2 O7‐ x (OV‐LZO) nanotubes with surface oxygen vacancies construct an efficient lithium polysulfides adsorption and catalysis network at the cathode/separator interface and a Li + transport network at the anode/separator interface to tackle the shuttle effect and lithium dendrite issues.